Diameter reduction of the great saphenous vein and the common femoral vein after CHIVA - Mendoza, E. (Phlebologie, 2013)
Introduction: The diameters of great saphenous vein (GSV) and common femoral vein (CFV) seem to give a hint about the severity of venous illness. A reduction of these diameters 8 weeks after CHIVA of GSV was demonstrated earlier (3), the longterm effect has not been published so far. As the GSV persists in situ and drains the leg blood through distal perforators into the deep vein, an overload oft he CFV after CHIVA has been postulated. The aim of this study is to discover long time effects of CHIVA on diameters of CFV.Methods: 43 Patients included in the first trial was explored 5 years after CHIVA of GSV or SSV. Diameters were measured in standing position: CFV diameter immediately after the confluence with the GSV and GSV diameter 15 cm distally to the groin. Clinic class (CEAP) and refilling time were compared to preoperative values and values after 8 weeks.Results: 43 patients (mean age 52.7 years) were explored 5.36 years after CHIVA operation of their saphenous veins. Diameter of CFV was reduced from preoperative 15.39 ± 2.93 mm (15.11 ± 2.73 after 8 weeks) to 14.18 ± 2.56 mm (p<0.05). In case of treatment of GSV the diameter of CFV changed from preoperative 16.07 ± 2.65mm through 15.29 ±0.41 mm after 8 weeks to 14.30 ± 2.81 mm (p<0.001). The diameter of GSV was reduced from 7.13 ± 2.05 mm pre-operative (4.98 ± 1.49 mm after 8 weeks) to 4.38 ± 1.44 mm after 5 years (p<0.001). The C class was reduced from 2.77 ± 0.81 preoperatively to 1.72 ± 1.10 after 5 years (p = 0.007). Refilling time was prolonged from preoperatively 15.24 ± 6.18s to 21.61 ± 9.2s after 5 years (p = 0.022).Conclusion: As already shown in the short term results, CHIVA reduced the caliber of the CFV and GSV as well as the C Class of CEAP and improved the refilling time. These results were also stable after 5 years.English version available at: www.phlebologieonline.de
Keywords: Varicose veins; CHIVA; vein diameter; long term results